Personal Branding Selebgram Traveller melalui Media Sosial pada Akun Instagram @Dewi_Faj - Putri Alfiani; Suryo, Herning; Sarungu, Lukas Maserona (Prodi Ilmu Komunikasi Universitas Sahid Surakarta, 2024)
This research was conducted to find out the personal branding of celebgrams through social media on the Instagram account @dewi_faj. This research aim to describe and analyze the personal branding carried out by Dewi Fajar Lestari via the Instagram account @dewi_faj. In this research, the author used eight main concepts in the formation of personal branding according to Peter Montoya dan Tim Vandehey, including specialization, leadership, personality, difference, visibility, constancy, visibility and good name. This type of research is qualitative with a descriptive analysis approach. Data collection methods used in-depth interviews and documentation. The result of this research was Dewi has built personal branding by implementing the 8 concepts above. Dewi has focused on the concept of specialization, so that it makes this research conclude that she success in building the personal branding as a beautiful and fashionable traveller, different with other nature travellers.